Belgische boeren in beeld: Een online databank van bewegend beeld over landbouw en platteland, 1920-1990 - Lefèvre, Sven; Segers, Yves (TSEG - The Low Countries Journal of Social and Economic History, 2021)
Belgian farmers in motion pictures. An online database with films on agriculture and countryside, 1920-1990.Since its breakthrough as a mass medium, film has exerted a major influence on society. Not only as a form of entertainment, but also as a mode of mass communication accompanied with great educational aspirations. Agriculture and the rural countryside have been the subject as well as the target audience of many so called ‘rural films’, produced by government administrations and civil society organizations, trying to influence rural politics and modernize daily farming practices. The ‘Cinema Rural’-database, presented in this article, makes it possible for researchers to access the metadata of almost a thousand rural films kept in Belgian collections. By doing so, the Centre for Agrarian History (KU Leuven) wants to encourage the use of these films in further research in agricultural and rural history.